A European aerosol phenomenology -4: Harmonized concentrations of carbonaceous aerosol at 10 regional background sites across Europe. (November 2016) - Cavalli, F.; Alastuey, A.; Areskoug, H.; Ceburnis, D.; Čech, J.; Genberg, J.; Harrison, R.M.; Jaffrezo, J.L.; Kiss, G.; Laj, P.; Mihalopoulos, N.; Perez, N.; et al.
Abstract: Although particulate organic and elemental carbon (OC and EC) are important constituents of the suspended atmospheric particulate matter (PM), measurements of OC and EC are much less common and more uncertain than measurements of e.g. the ionic components of PM. In the framework of atmospheric research infrastructures supported by the European Union, actions have been undertaken to determine and mitigate sampling artefacts, and assess the comparability of OC and EC data obtained in a network of 10 atmospheric observatories across Europe. Positive sampling artefacts (from 0.4 to 2.8 μg C/m 3 ) and analytical discrepancies (between −50% and +40% for the EC/TC ratio) have been taken into account to generate a robust data set, from which we established the phenomenology of carbonaceous aerosols at regional background sites in Europe. Across the network, TC and EC annual average concentrations range from 0.4 to 9 μg C/m 3, and from 0.1 to 2 μg C/m 3, respectively. TC/PM10 annual mean ratios range from 0.11 at a Mediterranean site to 0.34 at the most polluted continental site, and TC/PM2.5 ratios are slightly greater at all sites (0.15–0.42). EC/TC annual mean ratios range from 0.10 to 0.22, and do not depend much on PM concentration levels, especially in winter. Seasonal variations in PM and TC concentrations, and in TC/PM and EC/TC ratios, differ across the network, which can be explained by seasonal changes in PM source contributions at some sites. Highlights: Artefacts bias the sampling of carbonaceous matter by quartz fibre filters. Identical thermal protocols run on various instruments produce different results. Seasonal variations can be observed in intensive carbonaceous aerosol variables. TC/PM10 ratios range from 12 to 34% across European regional background sites. Site-mean EC/TC ratios range from 10 to 22% and get similar at all sites in winter.